Analysis of road sprint cycling performance - Menaspa, P. (2015)
Sprint cycling ability is a key determinant of road cycling performance, with many races designed specifically for sprinters. The ability to excel in the final sprint is relevant for both individual riders and teams. Despite the importance of sprints within professional road cycling, the characteristics of professional road sprints and sprinters have yet to be extensively described. Thus, the overall objective of the five research studies contained within this doctoral thesis was to describe road cycling sprint performance and improve the general understanding of the physical, technical and tactical factors associated with such performances. The first two descriptive field studies document the physical and physiological demand of sprint races during actual road cycling competitions. Specifically, Study 1 was designed to quantify the demands of sprinting in the male professional category. Seventeen competitions from six male professional cyclists (mean ± SD: age, 27.0 ± 3.8 y; height, 1.76 ± 0.03 m; weight, 71.7 ± 1.1 kg) who placed Top 5 in professional road races were analysed. Calibrated SRM power meters were used to monitor power output, cadence and heart rate. Data were averaged over the entire race, different durations prior to the sprint (60, 10, 5 and 1 min) and during the actual sprint. Variations in power during the final 10 min of the race were quantified using Exposure Variation Analysis. Power, cadence and heart rate were different between various phases of the race, increasing from 316 ± 43 W, 95 ± 4 rpm and 88 ± 3 % of maximal heart rate in the last 10 min to 487 ± 58 W, 102 ± 6 rpm and 96 ± 2 % of maximal heart rate in the last minute prior to the sprint. The peak power during the sprint was 17.4 ± 1.7 W·kg-1. Exposure Variation Analysis revealed a significantly greater number of short duration and high intensity efforts in the final five minutes of the race, compared with the penultimate five minutes (p=0.01). These findings quantified the power output requirements associated with high level sprinting in men`s professional road cycling and highlighted the need for both aerobic and anaerobic fitness. In Study 2, the characteristics of successful road sprints in professional and under 23 y male cycling races were compared. As in Study 1, Study 2 also described the exercise intensity for the sprinters throughout final 10 min of the race. Nine successful (Top 3) sprints performed by a professional (PRO: 23 y, 1.76 m, 71.8 kg) and an under 23 (U23: 18 y, 1.67 m, 63.2 kg) cyclist sprinter were analysed in this study. No statisticaldifferences were found between PRO and U23 in the absolute peak power, mean power, duration and total work during the sprint (PRO: 1370 ± 51 W, 1120 ± 33 W, 14.5 ± 2.4 s, 16.2 ± 2.6 KJ; U23: 1318 ± 60 W, 1112 ± 68 W, 12.8 ± 1.1 s, 14.2 ± 1.4 KJ). However, the intensity of the race recorded in the last 10 min prior to the sprint was significantly higher in PRO compared with U23 (4.6 ± 0.3 and 3.7 ± 0.2 W·kg-1, respectively). Race duration, total elevation gain (TEG) and mean power were similar between PRO and U23. In conclusion, the physiological demands leading into road sprints (intensity of the last 10 min) were found to be higher in PRO compared to U23 races. Nevertheless, a similar sprint power output (> 2500 W·Ap-1 or > 15.5 W·kg-1 for approximately 14 s, with a peak power output > 3100 W·Ap-1 or > 19 W·kg-1; where Ap is Projected Frontal Area) indicates that sprint characteristics may be similar in PRO and U23. As a result of the findings observed in the first two studies of this thesis, Study 3 was designed to better understand the effects of variable and non-variable exercises that replicate the intensity of the final portion of road competitions on maximal sprint performance. In this laboratory trial, ten internationally competitive male cyclists (age, 20.1 ± 1.3 y; height, 1.81 ± 0.07 m weight, 69.5 ± 4.9 kg; and VO2max, 72.5 ± 4.4 ml·kg-1·min-1) performed a 12-s maximal sprint in a rested state and again following: i) 10 min of non-variable cycling, and ii) 10 min of variable cycling. Variable and non-variable trials were conducted in a randomized, crossover fashion. The intensity during the 10 min efforts gradually increased to replicate the pacing observed in final sections of cycling road races. During the variable cycling subjects performed short (2 s) accelerations at 80% of their peak sprint power, every 30 s. Mean power output, cadence and heart rate during the 10 min efforts were similar between conditions (5.3 ± 0.2 W·kg-1, 102 ± 1 rpm, and 93 ± 3 %, respectively). Post exercise blood lactate concentration and perceived exertion immediately after exercise were also similar (8.3 ± 1.6 mmol·L-1, 15.4 ± 1.3 (6-20 scale), respectively). Peak and mean power output and cadence during the subsequent maximal sprint were not significantly different between the three experimental conditions (p=0.14). These results indicate that neither the variable nor the non-variable 10 min efforts performed within this study impaired the sprint performance in elite competitive cyclists. Due to the importance of the elevation gain variable in road cycling, the fourth study of this thesis was methodological and investigated the consistency of commercially available devices used to measure the TEG during races and training. This chapter was separated in two observational validation studies. Garmin (Forerunner 310XT, Edge 500 Edge 750 and Edge 800; with and without elevation correction) and SRM (Power Control 7) devices were used to measure TEG over a 15.7 km mountain climb performed on 6 separate occasions (6 devices; Study 4a) and during a 138 km cycling event (164 devices; Study 4b). TEG was significantly different between Garmin and SRM devices (p The final study of this thesis was an analysis of technical and tactical factors that influence sprint performance in professional competitions; particular focus was put on the TEG which was a factor identified as a potential cause of fatigue. More specifically, the subject of Study 5 was the highest international ranked professional male road sprint cyclist during the 2008-2011 seasons. Grand Tour sprint stages were classified as WON, LOST, or DROPPED from the front bunch prior to the sprint. Video of 31 stages were analysed for mean speed of the last km, sprint duration, position in the bunch and number of teammates at 60, 30, and 15 s remaining. Race distance, TEG and mean speed of 45 stages were determined. Head-to-head performances against the 2nd to 5th most successful professional sprint cyclists were also reviewed. Within the 52 Grand Tour sprint stages the subject started, he WON 30 (58%), LOST 15 (29%), was DROPPED in 6 (12%) and had one crash. Position in the bunch was closer to the front and the number of team members was significantly higher in WON compared to LOST at 60, 30 and 15 s remaining (p In conclusion, the general findings of this thesis were as follows: as expected, exercise intensity significantly increases in the last 10 min of relatively flat road races; there is a significantly greater number of short duration and high intensity efforts in the final 5 min of competitive road cycling races when compared with the penultimate 5 min; sprint duration and peak power output does not differ between PRO and U23 races and is approximately 13 s and 17 W·kg-1, respectively; the physiological demands in the 10 min before the sprint are higher in PRO compared to U23 races; neither a variable nor a non-variable 10 min lead up effort appears to impair the sprint performance of elite competitive cyclists; measurements of elevation gain are consistent within devices of the same brand, but differed between brands or when different settings were used; and technical and tactical aspects of road sprinting are related to performance outcomes.